KAJIAN FAKTOR PENDORONG KEAKTIFAN ORGANISASI DAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN BANK SAMPAH KOTA BANJARBARU KALIMANTAN SELATAN - Rizqi Puteri Mahyudin; Nailul Ummah; Muhammad Firmansyah (EnviroScienteae, 2018)
The purpose of this research is to analyze the best existing condition of four waste bank in Banjarbaru. They are Gemilang waste bank in Guntung Manggis, Sumber Rejeki waste bank in Syamsyudin Noor, Barokah waste bank in Landasan Ulin Timur, and Cempaka Putih waste bank in Sungai Ulin, in Banjarbaru city. The result of the analysis is the highest score of waste bank management is Sumber Rejeki waste bank, because the waste bank administrator socializes it intensively.